Risco de quedas em pessoas idosas hospitalizadas - Falção, Renata Maia de Medeiros (2018)
Introduction: Aging is a dynamic and progressive process that includes morphological, functional, social and psychological changes. In view of this, there is a greater number of frequent incidents in the third age, such as falls, often generating partial or total dependence on this elderly person, who needs specific care. Objective: to evaluate the risk of falls in hospitalized elderly patients. Methods: a descriptive cross-sectional study with a quantitative approach was carried out between April and October 2017 with 284 elderly patients hospitalized at the Clinic (Ala A and B), Surgical and Infectious-Parasitic Hospitals at a Public Teaching Hospital , located in the municipality of João Pessoa-PB. The Multivariate Correspondence Analysis technique was applied to evaluate the association between factors and the risk classification and the Chi-Square test to determine the risk categorization evaluated by the Morse Fall Scale. Study approved by the Ethics and Research Committee under opinion 2,193,755 and CAAE: n. 62128816.0.0000.5183. Results: Prevalence of male elderly, in the age group of 60 to 69 years, illiterate, pardos, married / stable union, with a monthly income of a minimum wage from retirement. It was identified that 45% of the elderly had a high risk of falls from and the Medical Clinic B was the hospitalization unit with the risk of falls higher according to the scores of the Morse Scale. The criteria of the secondary diagnostic scale and the use of intravenous therapy obtained a greater percentage of the elderly with high risk associated with falls. There was a significant association between the high risk of falls and urinary incontinence, impaired vision and the use of diuretic medications. Conclusion: The importance of assessing the risk of falls in the hospital environment was demonstrated, where the results found will help the health team in planning actions that reduce the risk of falls, providing a safer environment, with the help of specific tools that evaluate the risk of the hospitalized elderly person suffering this episode or not.